Nano-scaled semiconductor devices : physics, modelling and characterization - Gutierrez-D., Edmundo A. (Institution of Engineering and Technology, 2016)
This book describes methods for the characterisation, modelling, and simulation prediction of these second order effects in order to optimise performance, energy efficiency and new uses of nano-scaled semiconductor devices.
Keywords: Semiconductors.; Nanostructured materials.; elektronické knihy; electronic books